If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(7x + 32) + 33 = 0 Reorder the terms: x(32 + 7x) + 33 = 0 (32 * x + 7x * x) + 33 = 0 (32x + 7x2) + 33 = 0 Reorder the terms: 33 + 32x + 7x2 = 0 Solving 33 + 32x + 7x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + x)(11 + 7x) = 0Subproblem 1
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Subproblem 2
Set the factor '(11 + 7x)' equal to zero and attempt to solve: Simplifying 11 + 7x = 0 Solving 11 + 7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 7x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 7x = 0 + -11 7x = 0 + -11 Combine like terms: 0 + -11 = -11 7x = -11 Divide each side by '7'. x = -1.571428571 Simplifying x = -1.571428571Solution
x = {-3, -1.571428571}
| 2m=m+6 | | 5x^2+6x=31 | | -x-5=6 | | (n-4)*3=15 | | 20-c=12 | | 3(x+3)-2(x-1)=17 | | 7(x+2)=21 | | 11x-5=73 | | 2(x-5)+3(x-1)=32 | | (67-32)+8-7= | | 3a=12+a | | 2.9x+(-2)=8x+8 | | a^2+2a=35 | | -16t^2+112t+128= | | 10=12-2x | | z^2-12z=-20 | | 7+x=9-5x | | 6(x+1)-5(x-2)=20 | | 5x+1=6-3x | | 8x-8=3x-2 | | 16x^2+49= | | 0.5(0.3m+35n)-0.8(-0.09n-22m)= | | 81a^2-49= | | 25a^2-30a+9= | | 3x^3-12x^2+20x-12=0 | | r^2-12r+36= | | 3u^2+2u-21= | | s^3-2s^2+5s=0 | | 2r^2-9r+9= | | 2w^2+11w+5= | | 6x-18+2x=3x+17.6 | | (x-4)(x+3)+x=52 |